Philippines Economic Update, June 2021 : Navigating a Challenging Recovery - World Bank (World Bank, Washington, DC, 2021)
The resurgence of COVID-19 cases and reimposition of more stringent quarantine measures held back the early signs of an economic rebound. The downside risk of a resurgence of infection, identified in the PEU December 2020 edition, has unfortunately materialized. The number of daily cases increased from an average of 1,400 in December 2020 to nearly 10,000 in April 2021. The surging cases prompted the authorities to reimpose stricter quarantine measures in Metro Manila and nearby provinces for more than one-and-a-half months between April and May. Since then, daily cases have gone down gradually and critical care occupancy rates have eased. However, the quarantine and movement restrictions have hampered people's mobility, adversely affecting domestic activity. The economy contracted by 4.2 percent year-on-year in the first quarter of 2021 amid prolonged implementation of containment measures. The country registered the worst growth performance among peers in the region such as Thailand (-2.6 percent), Indonesia (-0.7 percent), Malaysia (-0.5 percent), and Vietnam (4.5 percent). The growth contraction was fueled by weak domestic demand, driven by the combination of containment measures, weak confidence, and rising inflation. Meanwhile, tepid external demand was driven by the sharp contraction in services exports amid lingering restrictions and weak demand for international tourism while goods exports recovered. The public sector was the main driver of growth with an expansionary budget. The authorities are supporting the economic recovery by accelerating public spending. Stimulus spending and infrastructure investment drove public spending from 19.1 percent of GDP in the first quarter of 2020 to 23.4 percent of GDP in the same period in 2021. The spending is in line with the continuing implementation of the pandemic response measures under the "Bayanihan to Recover as One" Law (Bayanihan 2) which was extended to June 30, 2021. The higher spending comes at a time when public revenues fell from 17.2 percent of GDP in the first quarter of 2020 to 16.0 percent of GDP in the same period in 2021. This resulted in an increase in the fiscal deficit to 7.4 percent of GDP in the first quarter of 2021 from 1.9 percent of GDP a year ago. The widening deficit was accompanied by an increase in the public debt ratio from 54.5 percent of GDP by end-2020 to 60.4 percent of GDP as of end-March 2021.